Nivel de satisfacción de las usuarias que reciben atención de enfermería en el servicio de gineco obstetricia del Hospital Provincial Alfredo Noboa Montenegro de la ciudad de Guaranda, provincia de Bolívar en el periodo agosto 2016 - enero 2017 - Chimbo Ordóñez, Adrián Paúl (2017)
Dear reader, please find this research titled; Level of satisfaction of users receiving nursing care in the Gineco obstetrics service of the provincial hospital Alfredo Noboa Montenegro of the city of Guaranda, province of bolivar in the period from August 2016 to January 2017, the same that consists of their approach to the problem Which says: What is the level of satisfaction of users receiving nursing care in the Gineco - Obstetrics service of the Hospital Alfredo Noboa Montenegro, followed by the general objective approach as follows: To determine the level of satisfaction of hospitalized users Who receive nursing care in the Gineco-Obstetrics service of the Hospital Alfredo Noboa Montenegro, assigning the following specific objectives: Characterize the target population (age, source and schooling). Identify the factors that determine the level of user satisfaction in: administration of drugs, techniques and procedures, communication, safety, comfort and hygiene, sleep, rest and education. Propose a plan for improving the quality of nursing care. The scientific framework makes studies related to this subject, then you will find the methodological strategies with their results, conclusions and recommendations and finally find the annexes of the results.